2007
DOI: 10.1177/1096348006297289
|View full text |Cite
|
Sign up to set email alerts
|

Does Combining Health Care Hospitality Services Increase Efficiency?

Abstract: Throughout the health care industry, managers of hospitality services are exploring potential efficiencies gained by merging departments in an attempt to leverage operational similarities with the goal of minimizing labor costs while maintaining or increasing customer satisfaction. Although the notion of optimizing operations by focusing on the service customer is central to general-system theorists, no extant studies assess whether such a practice applied to health care hospitality services enhances labor eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It also adds to the conversation surrounding the service excellence wording by suggesting HCSE as a higher form of service excellence only achievable through service excellence and HCP. Previous studies have been limited to discipline-based industry-specific inquiry, or relate to hospitality type support services of businesses in other industries (Reynolds and Leeman, 2007) while other studies brought a hospitality perspective described through only a service excellence realm (Ford et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also adds to the conversation surrounding the service excellence wording by suggesting HCSE as a higher form of service excellence only achievable through service excellence and HCP. Previous studies have been limited to discipline-based industry-specific inquiry, or relate to hospitality type support services of businesses in other industries (Reynolds and Leeman, 2007) while other studies brought a hospitality perspective described through only a service excellence realm (Ford et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The study suggested adding staff called a non-clinical concierge to be in charge of the planning, executing, and recovery of service for that wing further creating a job description for this position (Fottler et al, 2006). A more traditional recent hospitality research study by Reynolds and Leeman (2007) described how hospitality-based support services (e.g. foodservice, housekeeping, maintenance, and concierge) operated more efficiently when managed together.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Th ough few studies have directly studied hospitality as a philosophy applicable organisation wide, a recent hospital case study supported the importance of the alignment of the service mission statement with strategy, systems, and staffi ng (Ford et al, 2006;in Severt & Aiello, 2008, p. 666). A more traditional recent hospitality research study by Reynolds & Leeman (2007) described how hospitality-based support services (e.g. foodservice, housekeeping, maintenance, and concierge) operated more effi ciently when managed together.…”
Section: Medical Tourism and Hospitalitymentioning
confidence: 99%
“…A more traditional recent hospitality research study by Reynolds and Leeman (2007;in Severt & Aiello, 2008, p.666) described how hospitality-based support services (e.g. food service, housekeeping, maintenance, and concierge) operated more effi ciently when managed together.…”
Section: Hospitality In Hospitalmentioning
confidence: 99%
“…A range of 11% to 14% for input resource savings in these observed meal periods could be achieved. Reshaping the food ingredient size or outsourcing parts of the food preparation to the purveyor might be the solution to enhance the overall efficiency (Reynolds & Leeman, 2007).…”
Section: Conclusion and Future Researchmentioning
confidence: 99%